Competency-Based Budget Implementation Performance, Organizational Commitment, and Leadership - Rodiyah, Ainur; Sriyono, Sriyono; Hermawan, Sigit (Amkop Management Accounting Review (AMAR), 2025)
The Indonesian Budget, as a fiscal policy instrument in Indonesia, is aimed at promoting the prosperity of the people through government spending. However, in its implementation, there are problems in implementing the government budget, such as non-compliant financial management. This research focuses on the work unit of the First Level Religious Court in the East Java Region. Several work units have good budget management. However, there are several work units whose financial performance gets adequate marks and even approaches zero. However, in reality, work units are expected to manage their budgets efficiently and responsibly. Through a quantitative approach, this research aims to determine whether competence, organizational commitment, and leadership influence the financial performance of the First Level Religious Court work unit in the East Java Region.